Hypothesis: Efficacy of early treatments with some NSAIDs in COVID‐19: Might it also depend on their direct and/or indirect zinc chelating ability?. (8th December 2022) - Zamai, Loris
Abstract : The present work argues for the involvement of the zinc chelating ability of some non‐steroidal anti‐inflammatory drugs as an additive mechanism able to increase their efficacy against COVID‐19.